1986
DOI: 10.2105/ajph.76.10.1202
|View full text |Cite
|
Sign up to set email alerts
|

Planning for community physician services prior to deinstitutionalization of mentally retarded persons.

Abstract: This study assessed the need for physician services among a group of institutionalized mentally retarded individuals in anticipation of their transfer to community residential facilities and subsequent management of their care by community-based physicians. The clients' personal physicians in the institution identified every chronic condition which required physician services, and recommended the kind of physician and frequency of visits for the management of each condition. Key informants reviewed these estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1

Year Published

1987
1987
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 9 publications
1
22
1
Order By: Relevance
“…With respect to assessment, our data suggest that it might be important to monitor pain indicators on a daily basis so that proactive steps could be taken to prevent the emergence of problem behavior related to ongoing pain and discomfort associated with illness. This practice might be especially important given that people with developmental disabilities are more prone to illness, both chronic and acute, than the general population (Cooper, 1998;Minihan, 1986). Of considerable significance is the fact that the main method typically used for ascertaining the presence and intensity of illness-related pain, namely, patient interview, is not applicable to many people with developmental disabilities owing to their poor communicative skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to assessment, our data suggest that it might be important to monitor pain indicators on a daily basis so that proactive steps could be taken to prevent the emergence of problem behavior related to ongoing pain and discomfort associated with illness. This practice might be especially important given that people with developmental disabilities are more prone to illness, both chronic and acute, than the general population (Cooper, 1998;Minihan, 1986). Of considerable significance is the fact that the main method typically used for ascertaining the presence and intensity of illness-related pain, namely, patient interview, is not applicable to many people with developmental disabilities owing to their poor communicative skills.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a number of studies have documented substantially higher rates of both chronic and acute medical conditions in people with developmental disabilities as compared to the general population. Thus, Minihan (1986) found that 99% of individuals in a state institution had at least one chronic medical condition requiring regular followup (e.g., cardiac conditions, diabetes, ulcers, chronic otitis media, recurrent pneumonia, and progressive renal failure). Asberg (1989) noted that 80% of people with developmental disabilities admitted to hospitals in Uppsala, Sweden had at least one chronic medical condition and that the rate of hospital admission for people with developmental disabilities was three times that of the general population.…”
mentioning
confidence: 99%
“…Further, there is much evidence to show that among the population with ID, the average number of medical problems per person is about 5, which is many more than the figure for their peers in the general population (Beange et al, 1995;Wallace, 2001). Moreover, more than half of these medical conditions, if present in a patient without ID, would normally require the services of a specialised, hospital-based health professional (Beange et al, 1995;Kapell et al, 1998;Minihan, 1986).…”
Section: Morbidity and Mortalitymentioning
confidence: 99%
“…1 A young adult with mild mental retardation had received residential and vocational services from a voluntary service agency for over 15 years. His homosexual behavior was accepted by the agency's administration because it did not adversely affect his eligibility to receive these services.…”
Section: Of Infection With Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%